شبكة الزمر البوليانية المنتهية (LBG) (Latakia University Journal -Basic Sciences Series, 2018)
إن الهدف من هذا العمل هو دراسة الزمرة البوليانية المنتهية والتي تعرف بأنها الزمرة التي فيها كل عنصر x رتبته 2 ، وقد أثبتنا أن رتبة الزمرة البوليانية المولدة بـ n عنصراً هي  , سنرمز للزمرة البوليانية من الرتبة   بالرمز  , كما أثبتنا أن كل زمرة بوليانية من الرتبة  ايزومورفية مع الزمرة . وفي هذه الحالة فإن كل عنصر من عناصر الزمرة البوليانية يمكن التعبير عنه كمتتالية من n مركبة عناصرها من  , وبينّّا كذلك أن كل زمرة بوليانية هي زمرة مرتبة بعملية ترتيب   ثم إن كل زمرة بوليانية  هي شبكة مع العمليتين      إثبات أنها شبكة بوليانية . The purpose of this paper is to study the finite Boolean group which is known as the group in which every element x has order 2. We proved that the Boolean group order was generated by n elements is  . We  refer to the Boolean group from order  as   . In addition, we proved that every Boolean group from order  was an isomorphism with the group . So, in this situation every element of the Boolean group  can be represented as a sequence of  n projection whose elements are of . We also showed that the Boolean group is an organized group by the order operation. Thus, every Boolean is a lattice with two operations   . This proves that it is a Boolean lattice.